Analisis Sentimen Pemberitaan Vaksin Covid-19 dan Kaitannya dengan Perubahan Harga Saham Emiten Farmasi - Rai, Abyan (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2021)
Pandemic of Covid-19 that entered Indonesia in early March 2021 limited activities in various sectors. This condition causes the economy in Indonesia to become unstable and even experience a recession in 2020. Vaccines produced by pharmaceutical companies are one of the government's ways to improve not only health but also economic conditions in Indonesia. Various reports on the Covid-19 vaccine have caused investor reactions in the capital market, one of which is in the pharmaceutical sector itself as a producer of the Covid-19 vaccine. Using the Lexicon-based method and Pearson correlation, this study aims to analyze the sentiment of the Covid-19 vaccine coverage and analyze the relationship between these sentiments and the stock price of pharmaceutical issuers. Covid-19 vaccine news data is collected from Twitter for 22 days with 500 tweets per day. The tweets were categorized into positive, negative, or neutral sentiments using the Lexicon-based method. The results of this study indicate that the media provides more positive sentiment towards the Covid-19 vaccine. A unidirectional relationship exists between the sentiment in the Covid-19 vaccine coverage and one of the stock prices of a pharmaceutical issuer.